Susceptor
A susceptor with a SiC-coated carbon composite surface, polished using a kneading integrated lapping sheet, addresses uneven polishing and contamination issues, ensuring precise surface control and reduced impurity exposure.
Patent Information
- Application Number
- JP2024168043
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2041-09-21
AI Technical Summary
Existing susceptors used in epitaxial film deposition systems face issues with uneven polishing and contamination due to hard SiC coatings, which can damage wafers and introduce metal impurities during polishing.
A susceptor with a carbon composite material surface coated in a thin film of silicon carbide (SiC) is polished using a kneading integrated lapping sheet with diamond abrasive grains in a flexible heat-resistant resin, ensuring precise control of surface roughness and reducing metal impurity contamination.
The solution provides a susceptor with controlled surface roughness and reduced contamination, preventing wafer damage and maintaining polishing efficiency by self-growth of abrasive grains, while minimizing metal impurities.
Smart Images

Figure 2024174085000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to Susceptor For example, a wafer is held in an epitaxial film forming apparatus. Susceptor Regarding. [Background technology]
[0002] In epitaxial deposition equipment, which is one type of equipment used in semiconductor manufacturing, a carbon composite material made of a carbon material (called a carbon substrate) covered with silicon carbide (SiC) is used as a susceptor, which is a member that holds silicon wafers. There are several types of susceptors in use, including a single-wafer susceptor in which a recess for accommodating a single wafer is formed in a flat susceptor substrate, and a susceptor in which multiple recesses are formed. When manufacturing the susceptor, regardless of the type, the carbon substrate is placed in a designated coating furnace, and a silicon carbide (SiC) film is formed on the surface of the carbon substrate by a CVD method or the like to obtain a susceptor made of a carbon composite material.
[0003] 5, in the case of a single-wafer type susceptor, one main surface of a susceptor 50 is formed with a concave countersunk portion 51 for placing a silicon wafer W thereon. The silicon wafer W is supported by the susceptor 50 by contacting the peripheral portion of the countersunk portion 51. The peripheral portion within the countersunk portion 51 with which the silicon wafer W contacts is called a ledge portion 51a. For example, in Patent Document 1, the susceptor is manufactured by coating a carbon base material having recesses formed therein by mechanical grinding or the like with SiC, and the susceptor is used in a coated state for heat treatment of silicon wafers. However, when the SiC coating is used in a heat treatment or the like while it is coated with the SiC coating as in Patent Document 1, there is a risk that the top of the crystal acts like a blade and scratches the surface of the silicon wafer when the crystal grains become large, since SiC is very hard. To solve such problems, for example, in Patent Document 2, diamond paper and diamond paste are attached to the tip of a rotary polishing device, and the surface of the countersunk portion including the ledge portion is polished to adjust the surface roughness. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 56-10921 [Patent Document 2] Japanese Patent Application Publication No. 5-283351 Summary of the Invention [Problem to be solved by the invention]
[0005] In the polishing device disclosed in Patent Document 2, diamond paper 71 is attached to a polishing head 70 (rotating surface) at the tip as shown in Fig. 6. The diamond paper 71 is generally made by providing a layer of thermosetting synthetic resin 73 such as a resinoid bond on a resin base material 72, with diamond abrasive grains 74 held in the layer.
[0006] However, when polishing with this diamond paper 71, the abrasive grains 74 are held by the hard resin layer 73, so if there is distortion on the surface of the recessed portion, the abrasive grain surface may not contact evenly, which may result in uneven polishing. Furthermore, since the diamond abrasive grains 74 are held only on the surface side of the hard resin layer 73, if the diamond abrasive grains 74 fall off, the area where the diamond abrasive grains 74 fell off will be devoid of abrasive grains, which could cause problems such as a significant drop in the polishing rate.
[0007] In addition, it is known that the resinoid bond used in the diamond paper 71 contains a high concentration of metal impurities. In the research of the present inventor, it was found that if the polishing device contains metal impurities, the metal impurities remain in the countersunk portion, and there is a problem that it takes time and effort to remove the impurities after polishing.
[0008] The present invention has been made under the above circumstances, and provides a susceptor made of a carbon composite material in which the surface of a base material made of a carbon material is covered with a thin film of silicon carbide (SiC), which makes it possible to precisely control the surface roughness of at least the wafer holding surface including the ledge portion where the silicon wafer comes into contact with the susceptor, thereby preventing uneven polishing and suppressing contamination. Susceptor The purpose is to provide. [Means for solving the problem]
[0009] In addition, the susceptor according to the present invention, which has been made to solve the above problems, comprises: A susceptor having a base material made of a carbon material, the entire surface of which is covered with a thin film made of silicon carbide, and a ledge portion on one side of which is an annular region on which a silicon wafer is placed, the surface of the thin film of the ledge portion being a polished surface, the surface of the thin film of the ledge portion being free of protrusions of 20 μm or more, and the variation in surface roughness Sa of the thin film of the ledge portion being within 0.4 μm, and the concentration of Fe, Cr, Cu, and Al at a depth of 3 μm from the surface of the thin film in the ledge portion being 1×10 15 atoms / cm 3 Is less than or equal to It is characterized by: Here, it is preferable that a countersunk portion is formed on one surface side of the susceptor, and the countersunk portion has the ledge portion.
[0010] With a susceptor configured in this manner, when a silicon wafer is placed on the susceptor and a heat treatment is performed to form an epitaxial film on the upper surface of the wafer, the gap between the ledge portion and the lower surface of the silicon wafer can be reduced, and the growth of unnecessary epitaxial film on the lower surface (rear surface) of the silicon wafer can be suppressed. Also, contamination of silicon wafers with impurity metals can be reduced.
[0011] In order to solve the above problems, the manufacturing process of the susceptor according to the present invention includes the steps of forming a thin film made of silicon carbide on the entire surface of a substrate, and polishing the thin film on the surface on which the silicon wafer is placed. In the step of polishing the thin film, a kneaded integrated lapping sheet is attached to a rotatable polishing head, in which diamond abrasive grains and a heat-resistant resin are kneaded together and the diamond abrasive grains are arranged in multiple layers in the heat-resistant resin. The polishing head is rotated, and the kneaded integrated lapping sheet is pressed against the thin film to perform the polishing process. In addition, it is preferable that the thickness of the kneaded integrated lapping sheet is 60 μm or more and 90 μm or less, and the grain size of the diamond abrasive grains is 10 μm or more and 40 μm or less. In addition, it is preferable that the heat-resistant resin is any one of polyimide resin, polyethylene resin, polyethylene terephthalate resin, polyamide resin, and polypropylene resin.
[0012] According to this method, in a susceptor made of a carbon composite material in which the surface of a base material made of a carbon material is covered with a thin film of silicon carbide (SiC), at least the ledge portion with which the silicon wafer comes into contact is polished using an integrated lapping sheet made of a flexible heat-resistant resin and diamond abrasive grains kneaded together to form a sheet, thereby enabling the surface roughness to be precisely controlled. In other words, if diamond abrasive grains fall off from the surface of the kneaded integrated lapping sheet during the polishing process, other diamond abrasive grains will be present underneath the fallen diamond abrasive grains, and these will come out (grow spontaneously) to the surface side of the sheet when pressure is applied to the surface to be polished, thereby maintaining the polishing power for a long time and preventing a decrease in the polishing rate. Furthermore, if the kneaded integrated lapping sheet is flexible and further supported by a cushioning material, even if the surface to be polished is distorted, the abrasive grain surface will fit and contact the surface evenly, thereby preventing uneven polishing. Furthermore, in the kneaded and integrated wrapping sheet, the heat-resistant resin has a low concentration of metal impurities, so that no metal impurities remain in the recessed portion, making it unnecessary to carry out the step of removing impurities after polishing. The heat-resistant resin is not particularly limited as long as it is an engineering plastic (general-purpose engineering plastic, super engineering plastic) or a general-purpose plastic, but it is more preferable that the heat-resistant resin is any one of polyimide resin, polyethylene resin, polyethylene terephthalate resin, polyamide resin, and polypropylene resin, since they are heat resistant and can be formed into a sheet. Effect of the Invention
[0013] According to the present invention, in a susceptor made of a carbon composite material in which the surface of a base material made of a carbon material is covered with a thin film of silicon carbide (SiC), the surface roughness of the wafer holding surface including at least the ledge portion where the silicon wafer comes into contact with the susceptor can be controlled with high precision, and contamination can be suppressed without causing uneven polishing. Susceptor can be provided. [Brief description of the drawings]
[0014] [Figure 1] FIG. 1 is a cross-sectional view that illustrates a CVD apparatus used in manufacturing a susceptor according to the present invention. [Diagram 2] FIG. 2 is a cross-sectional view of a susceptor formed by processing in the CVD apparatus of FIG. [Diagram 3] FIG. 3 is a cross-sectional view showing the configuration of the polishing apparatus. [Figure 4] FIG. 4 is a cross-sectional view showing a state of a polishing process by the polishing apparatus. [Diagram 5] FIG. 5 is a cross-sectional view showing the configuration of a conventional single-wafer susceptor. [Figure 6] FIG. 6 is a cross-sectional view showing the configuration of a conventional polishing apparatus. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The following is a description of the present invention. Susceptor An embodiment of the present invention will be described with reference to Figures 1 to 4. The figures are schematic or conceptual, and the relationship between the thickness and width of each portion, the size ratio between portions, etc. are not accurately illustrated.
[0016] In the susceptor according to the present invention, first, a silicon carbide (SiC) film is formed on the surface of a carbon substrate using, for example, a CVD apparatus 5 as shown in FIG. 1 includes a chamber 10 that forms a processing space, a gas inlet 11 provided on a side surface of the chamber 10 for supplying a carrier gas (hydrogen gas) into the chamber 10, and a gas outlet 12 provided on a side surface of the chamber 10 opposite the inlet 11. The CVD apparatus 5 also includes a support section 20 for supporting the lower surface side of the carbon substrate 2 of the susceptor in the chamber 10. Heater sections 15 are provided above and below the chamber 10, and are configured to be able to heat the interior of the furnace to a predetermined temperature.
[0017] When manufacturing a susceptor using this CVD apparatus 5, a carbon substrate 2 made of a carbon material with a circular countersunk portion 4 formed in advance is placed on a support portion 20 in a chamber 10. The carbon substrate 2 is for use with, for example, 4-, 5-, 6-, 8-, or 12-inch silicon wafers with a diameter of 50 to 400 mm, and has internal impurity concentrations (metal elements Fe, Ni, and Cr) of 0.05 ppm or less.
[0018] Moreover, the heater unit 15 is driven to raise the temperature inside the chamber 10 to, for example, 500° C., and the inside of the chamber 10 is evacuated through the gas outlet 12 to create a vacuum state. Next, a carrier gas (H2) is introduced into the chamber 10 at a predetermined flow rate from the gas inlet 11. Thereafter, the temperature inside the chamber 10 is raised to, for example, 1300°C, and the source gas (SiCl4, C3H8) is introduced for a predetermined time using H2 as a carrier gas (dilution gas). The source gas concentration inside the chamber 10 at the start of the introduction is, for example, 15% to 20%.
[0019] Then, the source gas is supplied into the chamber 10 for a predetermined time (e.g., 14 hours) so that the formed film has a predetermined thickness (e.g., 60 μm or more). The source gas flows along the upper and lower surfaces of the carbon substrate 2 by the carrier gas, and is discharged from the gas outlet 12. When a preset supply time of the source gas has elapsed, the supply of the source gas is stopped.
[0020] Through these treatments, a thin film 3 made of silicon carbide (SiC) is formed on the carbon substrate 2 as shown in FIG. Next, the carbon base material 2 on which the thin film 3 is formed is taken out of the chamber 10, and a polishing process is performed on the countersunk portion 4. Here, the polishing process is performed on at least the ledge portion 4a which is the contact portion with the silicon wafer W in the countersunk portion 4. 3, the polishing device 6 used in this polishing process is provided with a buffer member 9 such as urethane rubber on a polishing head (rotating base material) 7b supported by a rotating shaft 7a, and further provided with a kneaded integrated lapping sheet 8 on the buffer member 9. The thickness Tk1 of the buffer member 9 is, for example, 5 mm.
[0021] The kneaded integrated wrapping sheet 8 is made by kneading diamond abrasive grains 8a with a flexible heat-resistant resin 8b such as polyimide, and the diamond abrasive grains 8a are arranged in multiple layers in the heat-resistant resin 8b as shown in FIG. 3. As described above, the heat-resistant resin can be any engineering plastic (general-purpose engineering plastic, super engineering plastic) or general-purpose plastic without any particular limitation. More preferably, the heat-resistant resin is any of polyimide resin, polyethylene resin, polyethylene terephthalate resin, polyamide resin, and polypropylene resin, since they are heat-resistant and can be formed into a sheet.
[0022] More specifically, the diamond abrasive grains 8a are contained in the heat-resistant resin 8b with a concentration of 20 to 200, more preferably 70 to 130 (for example, 100), and the diamond abrasive grains 8a are arranged substantially uniformly in the sheet surface direction and thickness direction in the sheet-like heat-resistant resin 8b. The diamond abrasive grains 8a arranged on the sheet surface have a high holding force when the heat-resistant resin 8b is, for example, a polyimide resin. However, it is expected that the diamond abrasive grains 8a on the surface of the sheet will fall off due to the wear of the heat-resistant resin 8b during polishing. In that case, other diamond abrasive grains 8a will be present under the fallen diamond abrasive grains 8a, and these will newly emerge (grow naturally) on the surface side of the consumable sheet 8, so that the polishing power can be maintained for a long time and the decrease in the polishing rate can be suppressed.
[0023] The kneaded integrated wrapping sheet 8 is preferably formed to have a thickness Tk2 of 60 μm or more and 90 μm or less (e.g., 75 μm). If the thickness Tk2 of the kneaded integrated wrapping sheet 8 is less than 60 μm, it may be worn away and lost during polishing, and if it is more than 90 μm, it will lose flexibility and will not be able to follow the unevenness of the product (susceptor), which is not preferable. The area of the kneaded wrapping sheet 8 is, for example, 0.5 cm 2 is formed.
[0024] The grain size of the diamond abrasive grains 8a is selected depending on the target value of the surface roughness Sa of the surface to be polished (target surface roughness Sa value). For example, when the target surface roughness Sa is small, 1.0 μm or less, diamond abrasive grains 8a with a grain size of 30 to 40 μm are used, and when the target surface roughness Sa is larger than 1.0 μm, diamond abrasive grains 8a with a grain size of 10 to 20 μm are used. In this embodiment, the grain size of the diamond abrasive grains 8a is preferably 10 μm or more and 40 μm or less. If the grain size of the diamond abrasive grains 8a is smaller than 10 μm, the polishing efficiency will be extremely poor, and if the grain size of the diamond abrasive grains 8a is larger than 40 μm, tool marks (scratches) will remain on the polished part, which is not preferable.
[0025] Furthermore, since the lapping sheet 8 is flexible and is held by a cushioning material 9 such as urethane rubber, even if the surface to be polished is distorted, the abrasive surface fits and contacts the surface evenly, preventing uneven polishing. In addition, since diamond paper using a resinoid bond as in the conventional method is not used and the concentration of metal impurities in the heat-resistant resin 8b is low, no metal impurities remain in the recessed portion 4, making it possible to eliminate the need for the work of removing impurities after polishing.
[0026] 4, the polishing is performed for 2 minutes by pressing a kneaded integral lapping sheet 8 against the ledge 4a of the countersunk portion 4 with a pressure of 2 kgf and setting the polishing head rotation speed to 2000 rpm. After the polishing is completed, the final susceptor is obtained by cleaning with hydrofluoric and nitric acids.
[0027] In the susceptor thus obtained, at least the ledge portion 4a, which is the annular region in the recessed portion 4 that contacts the underside of the silicon wafer W, is formed so that the variation in surface roughness Sa (arithmetic mean roughness of the surface) of the thin film 3 is within 0.4 μm. That is, when the silicon wafer W is placed on the susceptor and a heat treatment is performed to form an epitaxial film on the upper surface of the wafer, the gap between the ledge portion 4a and the lower surface of the silicon wafer W can be reduced, and the growth of unnecessary epitaxial film on the lower surface (rear surface) of the silicon wafer W can be suppressed.
[0028] Furthermore, since the above-mentioned polishing process is performed on the ledge portion 4a of the silicon wafer W, there are no protrusions of, for example, 20 μm or more on the surface of the thin film 3. This prevents the surface of the silicon wafer W from being damaged by the protrusions on the susceptor 1 side. As described above, in the case of the heat-resistant resin 8b, the concentration of metal impurities is low, so that no metal impurities remain in the countersunk portion 4. Therefore, the content of metal impurities (Fe, Cr, Cu, Al) in the measurement area of 200 μm×200 μm at a depth of 3 μm from the surface of the thin film 3F in the ledge portion 4a is 1×10 15 atoms / cm 3 This reduces contamination of silicon wafers with impurity metals.
[0029] As described above, according to the embodiment of the present invention, in a susceptor made of a carbon composite material in which the surface of a substrate 2 made of a carbon material is covered with a thin film 3 of silicon carbide (SiC), at least the ledge portion 4a with which the silicon wafer W comes into contact is polished with the kneaded integrated lapping sheet 8, thereby enabling the surface roughness to be precisely controlled. In other words, if diamond abrasive grains 8a fall off from the surface of the kneaded integrated lapping sheet 8 during the polishing process, new abrasive grains 8a will grow from underneath one after another, thereby preventing a decrease in the polishing rate.
[0030] Furthermore, since the kneaded integrated lapping sheet 8 is flexible and is held by a cushioning material 9 such as urethane rubber, even if the surface to be polished is distorted, the abrasive surface fits and contacts the surface evenly, preventing uneven polishing. Furthermore, in the kneaded integrated wrapping sheet 8, the heat-resistant resin 8b has a low concentration of metal impurities, so that no metal impurities remain in the recessed portion 4, making it possible to eliminate the need for the task of removing impurities after polishing.
[0031] In the above embodiment, the kneaded integrated lapping sheet 8 is placed on the cushioning member 9 in the polishing device 6, but the present invention is not limited to this configuration, and the configuration may also be such that the cushioning member 9 is not provided. In addition, in the above embodiment, a susceptor having a recessed portion is described as an example, but the present invention is not limited to this form and can also be applied to a susceptor that does not have a recessed portion. Furthermore, in the case where a countersunk portion is provided, the present invention is not limited to a countersunk portion curved in a concave shape as shown in the drawings, and can also be applied to a susceptor having, for example, a cylindrical countersunk portion. EXAMPLES
[0032] The present invention Susceptor The above will be further explained based on examples. [Experiment 1] In experiment 1, it was verified whether the target surface roughness Sa (arithmetic mean roughness of the surface) could be obtained depending on the grain size of the diamond grains in the kneaded integrated lapping sheet used in the polishing device. Furthermore, 18 measurement points were randomly selected on the ledge of one susceptor, and the variation in surface roughness Sa was measured.
[0033] Example 1 In Example 1, isotropic graphite was used as the material of the susceptor substrate, and multiple carbon substrates with countersunk portions were prepared. Using the CVD apparatus shown in Figure 1, a silicon carbide film was formed on the substrate surface under multiple film thickness formation conditions. In the CVD apparatus, a carbon substrate was placed in a chamber, and after evacuation, the chamber was heated to 500°C and a carrier gas (H2) was introduced into the chamber. The chamber was then heated to 1300°C, and the carbon substrate was rotated at a rotation speed of 0.1 rpm so as not to fix the support position of the carbon substrate, and raw material gas (SiCl4, C3H8) was supplied along the front and back surfaces of the carbon substrate. After a predetermined time (14 hours), the supply of the raw material gas was stopped, and after 1 hour, the rotation of the carbon substrate was stopped to form a silicon carbide thin film having a thickness of 60 μm on the substrate surface.
[0034] Next, the ledge portion of the countersunk portion was polished for a certain period of time by rotating the susceptor using a polishing device with a polishing head equipped with the kneaded integrated lapping sheet shown in Figure 3. The conditions were: polishing pressure 2 kgf, polishing head rotation speed 2000 rpm, susceptor rotation speed 20 rpm, and polishing time 2 minutes. The kneaded integrated wrapping sheet is made of a flexible heat-resistant resin, polyimide resin, and is kneaded with powdered diamond abrasive grains to form a sheet having a thickness of 75 μm. The concentration of diamond abrasive grains in the polyimide resin is 100, and the grain size of diamond grains is 30 to 40 μm. The sheet area is 0.5 cm2. 2 It was decided.
[0035] The kneaded and integrated lapping sheet was attached to the polishing head via a 5 mm thick urethane rubber plate that served as a shock-absorbing member. After polishing, 18 measurement areas were randomly selected on the ledge of one susceptor, and the variation in surface roughness Sa was measured. The measurement method was to create a height profile of the measurement area using a laser microscope, and obtain the arithmetic mean roughness Sa of the surface in each measurement area. As a result of Example 1, the variation in the surface roughness Sa of the ledge was within 0.4 μm. Furthermore, as a result of observing the ledge with a laser microscope, no protrusions exceeding 20 μm were present.
[0036] Example 2 In Example 2, the diamond grain size contained in the kneaded integrated lapping sheet in the polishing process for the ledge portion was 10 to 20 μm. The other conditions were the same as those in Example 1. After polishing, 18 measurement areas were randomly selected on the ledge of one susceptor, and the variation in surface roughness Sa was measured. The measurement method was to create a height profile of the measurement area using a laser microscope, and obtain the arithmetic mean roughness Sa of the surface in each measurement area. As a result of Example 2, the variation in the surface roughness Sa of the ledge was within 0.4 μm. Furthermore, as a result of observing the ledge with a laser microscope, no protrusions exceeding 20 μm were present.
[0037] Comparative Example 1 In Comparative Example 1, isotropic graphite was used as the material of the susceptor substrate, and multiple carbon substrates with countersunk portions were prepared as in Example 1. Using the CVD apparatus shown in Fig. 3, silicon carbide films were formed on the substrate surfaces under multiple film thickness formation conditions. In the CVD apparatus, a carbon substrate was placed in a chamber, and after evacuation, the chamber was heated to 500°C and a carrier gas (H2) was introduced into the chamber. The chamber was then heated to 1300°C, and the carbon substrate was rotated at a rotation speed of 0.1 rpm so as not to fix the support position of the carbon substrate, and raw material gas (SiCl4, C3H8) was supplied along the front and back surfaces of the carbon substrate. After a predetermined time (14 hours), the supply of the raw material gas was stopped, and after 1 hour, the rotation of the carbon substrate was stopped to form a silicon carbide thin film having a thickness of 70 μm on the substrate surface.
[0038] Next, the ledge in the countersunk portion was polished for a certain period of time while rotating the susceptor and keeping the rotating polishing head fixed, using a polishing device with a polishing head equipped with diamond paper with diamond abrasive grains held in a resinoid bond (thermosetting synthetic resin) as shown in Figure 6. The conditions were: polishing pressure 2kgf, polishing head rotation speed 2000rpm, susceptor rotation speed 20rpm, and polishing time 1 minute. In the diamond paper, the diamond abrasive grains are arranged in one layer by a resinoid bond, the concentration of the diamond abrasive grains is 100, and the grain size of the diamond grains is 30 to 40 μm. The sheet area is 0.5 cm 2 It was decided. After polishing, 18 measurement areas were randomly selected on the ledge of one susceptor, and the variation in surface roughness Sa was measured. The measurement method was to create a height profile of the measurement area using a laser microscope, and obtain the arithmetic mean roughness Sa of the surface in each measurement area. As a result of Comparative Example 1, the variation in the surface roughness Sa of the ledge face was 0.5 μm or more.
[0039] As described above, the results of Experiment 1 confirmed that the variation in surface roughness Sa in the ledge portion was within 0.4 μm and could be kept small. It was also confirmed that the surface roughness Sa of the ledge changes depending on the grain size of the diamond abrasive grains, so it is sufficient to set the grain size of the abrasive grains according to the target surface roughness Sa. On the other hand, it was confirmed that in Comparative Example 1, the variation in surface roughness Sa at the ledge portion was greater than in Examples 1 and 2.
[0040] [Experiment 2] In experiment 2, it was verified whether the polished SiC film was contaminated with metal impurities on the ledge of the susceptor. In order to verify whether the polishing of the ledge portion causes contamination, first, a susceptor was manufactured without polishing the ledge portion, and the concentrations of Fe, Cr, Cu, and Al were measured in a measurement area of 200 μm×200 μm at a depth of 3 μm from the surface of the SiC film in the ledge portion. The measurement method used was secondary ion mass spectrometry (SIMS analysis). The manufacturing conditions of the susceptor were the same as those of Example 1, except that the ledge portion was not polished. As a result, the concentrations of Fe, Cr, Cu, and Al at a depth of 3 μm from the surface of the SiC film were 1×10 15 atoms / cm 3 The results were as follows.
[0041] Example 3 In Example 3, the concentrations of Fe, Cr, Cu, and Al were measured in a measurement area of 200 μm×200 μm at a depth of 3 μm from the surface of the SiC film in the ledge of a susceptor manufactured by the same method as in Example 1. Secondary ion mass spectrometry was used as the measurement method. As a result of Example 3, the concentrations of Fe, Cr, Cu, and Al at a depth of 3 μm from the surface of the SiC film were 1×10 15 atoms / cm 3 The results were as follows. That is, there was almost no contamination by metal impurities, even compared to the case where the ledge portion was not polished.
[0042] Example 4 In Example 4, the concentrations of Fe, Cr, Cu, and Al were measured in a measurement area of 200 μm×200 μm at a depth of 3 μm from the surface of the SiC film on the ledge of a susceptor manufactured by the same method as in Example 2. The measurement method was the same as in Example 3. As a result of Example 4, the concentrations of Fe, Cr, Cu, and Al at a depth of 3 μm from the surface of the SiC film were 1×10 15 atoms / cm 3 The results were as follows. That is, there was almost no contamination by metal impurities, even compared to the case where the ledge portion was not polished.
[0043] Comparative Example 2 In Comparative Example 2, the concentrations of Fe, Cr, Cu, and Al were measured in a measurement area of 200 μm×200 μm at a depth of 3 μm from the surface of the SiC film on the ledge of a susceptor manufactured by the same method as in Comparative Example 1. The measurement method was the same as in Example 3. As a result of Comparative Example 2, the concentrations of Fe, Cr, Cu, and Al at a depth of 3 μm from the surface of the SiC film were 1×10 16 More than 1×10 18 atoms / cm 3 The results were as follows. That is, it was confirmed that the polishing process caused contamination with metal impurities compared to the case where the ledge portion was not polished.
[0044] As a result of the above Experiment 2, according to Examples 3 and 4, the concentrations of Fe, Cr, Cu, and Al at a depth of 3 μm from the surface of the SiC film in the ledge of the susceptor were 1×10 15 atoms / cm 3 It was confirmed that this could be kept low. [Explanation of symbols]
[0045] 1. Susceptor 2 Carbon substrate 3. Thin Film 4 Counterbore 5 CVD equipment 6 Polishing equipment 8. Mixed and integrated wrapping sheet 8a Diamond abrasive grain 8b Heat-resistant resin 10. Chamber 11 Gas inlet 12 Gas outlet 20 Support part
Claims
1. A susceptor having a substrate made of a carbon material, the entire surface of which is coated with a thin film made of silicon carbide, and having a ledge portion on one side which is an annular region on which a silicon wafer is placed, the surface of the thin film of the ledge portion is a polished surface, and no protrusions of 20 μm or more are present on the surface of the thin film of the ledge portion; And the variation in surface roughness Sa of the thin film of the ledge portion is within 0.4 μm, The concentration of Fe, Cr, Cu, and Al at a depth of 3 μm from the surface of the thin film in the ledge portion is 1×10 15 atoms / cm 3 or less for each element. A susceptor comprising:
2. A susceptor as described in claim 1, characterized in that a recessed portion is formed on one side of the susceptor, and the recessed portion has the ledge portion.
Citation Information
Patent Citations
Susceptor for heat treatment of semiconductor wafer and its manufacture
JP1995335572A
Jig for heat treatment and surface protection film forming method therefor
JP2005159014A
Surface protection film formation method for repairing tool for heat treatment and repairing tool for heat treatment
JP2005197534A
Method for processing semiconductor processing parts and parts formed by this method
JP2006526894A
Susceptor for vapor deposition, and method for producing the same
JP2008174841A
